The Implantation and Transmission of Plague Culture by the Five Plague Gods in Shuilu Murals - Bao YI; Qian ZHOU; Honglei SHI; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. The Five Plague Gods (五瘟神) in the Shuilu (水陆) murals from the Ming and Qing dynasties exemplify a distinctive manifestation of plague gods image developed under the pedigree of Taoist gods. As a significant system for expelling disasters in Shuilu, the depiction of the Five Plague Gods prominently merges human beings and livestock. This shape form to a large extent, draws on the image of Nuo (傩), a figure reflecting an imagination of the host of plague pathogens. In terms of the numbers of gods, it aligns with the conceptual framework of Wu Xing (五行 the five elements), a foundational principle in traditional Chinese medicine. The internal cultural connection highlights the means of plague prevention and control in China, as well as the external reflection of plague culture. Through multi-dimensional interpretations with the double proof method, this article dissects the formation, core elements, and cultural characteristics of the beliefs in the Five Plague Gods reflected in the Shuilu murals, and transcends mere visual semantics, offering a deeper understanding of these complex cultural symbols.